Some questions training judicial reform 1864 - Рум’янцев, В. О. (Problems of legality, 2014)
The article analyzes the reasons of reforming the judicial system, reproduce the course elaboration of foundations for a new judicial system and judiciary, shows the struggle between liberal and conservative camps, considered the principles Judicial Reform in 1864.